2021
DOI: 10.3390/nu13103483
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Oxidative Stress and the Therapeutic Approaches to the Intake of Antioxidant Supplements and Physical Activity

Abstract: Reactive oxygen species (ROS) are strongly reactive chemical entities that include oxygen regulated by enzymatic and non-enzymatic antioxidant defense mechanisms. ROS contribute significantly to cell homeostasis in the heart by regulating cell proliferation, differentiation, and excitation-contraction coupling. When ROS generation surpasses the ability of the antioxidant defense mechanisms to buffer them, oxidative stress develops, resulting in cellular and molecular disorders and eventually in heart failure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 113 publications
4
9
0
Order By: Relevance
“…MDA as observed in this study previously demonstrated induction of oxidative stress [4,12,18,20]. This position was further supported by other studies [23,24,25].…”
supporting
confidence: 92%
“…MDA as observed in this study previously demonstrated induction of oxidative stress [4,12,18,20]. This position was further supported by other studies [23,24,25].…”
supporting
confidence: 92%
“…CVDs constitute disorders manifested by a chronic inflammatory state and alterations of the oxidant–antioxidant balance of the oxidative stress character [ 91 , 92 ]. It is common knowledge, however, that muscle activity during physical exercise leads to a significant increase in ROS concentration and improves the antioxidant defense system in the organism [ 93 , 94 ].…”
Section: Effects Of Physical Exercise On Redox Equilibrium In Cardiov...mentioning
confidence: 99%
“…As mentioned, CVDs are disorders characterized by oxidative stress and inflammation in the myocardium and blood vessels [ 91 , 92 ]. Oxidative stress may be both a primary and a secondary factor of many CVDs [ 106 ].…”
Section: Pathological Consequences Of Oxidative Stress In Cardiovascu...mentioning
confidence: 99%
“…For ease of reading, we divided the nutrients into four sections: Diets (ketogenic diet, hypocaloric diet), Macronutrients (fats/lipids, carbohydrates, proteins), Micronutrients (vitamins, minerals), and Phytochemicals/Phytonutrients. The markers of OS described in this review included ROS; products of oxidative damage in deoxyribonucleic acid (DNA), lipids, and proteins; and evaluation of endogenous components in pro-oxidative and antioxidative systems [ 7 ].…”
Section: Introductionmentioning
confidence: 99%